Online and offline victimisation: a cluster analysis of adolescent victims of bullying and cyber-bullying in Chile. Issue 4 (2nd October 2021) - Trajtenberg, Nicolás; Dodel, Matías; Sanchez De Ribera, Olga; Cabello, Patricio; Claro, Magdalena
ABSTRACT: Bullying and cyberbullying victimisation are serious problems worldwide, especially among children and adolescents. However, there is much research on risk factors, the evidence about victim typologies that combine online and offline bullying with the specific nature of the victimisation episodes and other sociodemographic and individual features is still scarce. This study contributes by combining the poly-victim framework with the cyberbullying and online risk approaches. We used data from the Kids Online survey conducted in 2016 and analysed a national sample of 1, 000 Internet users in Chile between 9 and 17 years old. The aim was to classify youth based on their cyber and traditional bullying experiences and examine the clusters' features based on age, sex, socioeconomic status, technology use and skills, risky offline behaviours and well-being. A two-step cluster analysis identified three groups: poly-victims (23%), occasional digital victims (30%), and frequent offline victims (41%). These groups significantly differed by age, sex, Internet use, digital skills, risky offline behaviours and psychological characteristics. These results highlight the heterogeneity and complexity of both traditional and cyberbullying and the need to tailor interventions for diverse types of victims. IMPACT SUMMARY a. Prior State of Knowledge: Bullying is a serious problem both in its traditional and cyber-forms. Both share commonalities and present divergences regarding risk factors and psychological consequences associated. Whereas they can be distinct types of victimisation, a significant percentage of victims suffer both. b. Novel Contributions: Frequent offline bullying, occasional digital victimisation, and poly-victimisation should be considered three victimisation forms. These three experiences differ significantly in their age and sex composition, Internet use, digital skills, risky offline behaviours and psychological characteristics. c. Practical Implications: Identification of victim groups is critical to developing a more tailored approach to support different victims and reduce various forms of harassment. Moreso, because the current impacts of bullying-prevention programs are relatively small.